Circadian Misalignment, Reward‐Related Brain Function, and Adolescent Alcohol Involvement. (29th January 2013) - Hasler, Brant P.; Clark, Duncan B.
<x xml:space="preserve">Abstract</x> Background Developmental changes in sleep and circadian rhythms that occur during adolescence may contribute to reward‐related brain dysfunction, and consequently increase the risk of alcohol use disorders (AUDs). Methods This review (i) describes marked changes in circadian rhythms, reward‐related behavior and brain function, and alcohol involvement that occur during adolescence, (ii) offers evidence that these parallel developmental changes are associated, and (iii) posits a conceptual model by which misalignment between sleep–wake timing and endogenous circadian timing may increase the risk of adolescent AUDs by altering reward‐related brain function. Results The timing of sleep shifts later throughout adolescence, in part due to developmental changes in endogenous circadian rhythms, which tend to become more delayed. This tendency for delayed sleep and circadian rhythms is at odds with early school start times during secondary education, leading to misalignment between many adolescents' sleep–wake schedules and their internal circadian timing. Circadian misalignment is associated with increased alcohol use and other risk‐taking behaviors, as well as sleep loss and sleep disturbance. Growing evidence indicates that circadian rhythms modulate the reward system, suggesting that circadian misalignment may impact adolescent alcohol involvement by altering reward‐related brain function. Neurocognitive function is also subject to sleep and circadian influence, and thus circadian misalignment may also impair inhibitory control and other cognitive processes relevant to alcohol use. Specifically, circadian misalignment may further exacerbate the cortical–subcortical imbalance within the reward circuit, an imbalance thought to explain increased risk‐taking and sensation‐seeking during adolescence. Adolescent alcohol use is highly contextualized, however, and thus studies testing this model will also need to consider factors that may influence both circadian misalignment and alcohol use. Conclusions This review highlights growing evidence supporting a path by which circadian misalignment may disrupt reward mechanisms, which may in turn accelerate the transition from alcohol use to AUDs in vulnerable adolescents.